2019
DOI: 10.5582/ddt.2019.01047
|View full text |Cite
|
Sign up to set email alerts
|

Induction of signal transduction pathways related to the pathogenicity of <i>Cryptococcus neoformans</i> in the host environment

Abstract: Cryptococcus neoformans, a human pathogenic fungus, infects immunocompromised humans and causes serious diseases such as cerebral meningitis. C. neoformans controls the expression of virulence factors in response to the host environment via various signal transduction pathways. Understanding the molecular mechanisms involved in C. neoformans infection will contribute to the development of methods to prevent and treat C. neoformans-related diseases. C. neoformans produces virulence factors, such as a polysaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In C. neoformans , the calcineurin pathway is involved in capsule production and melanin synthesis, which are responsible for evading host immunity 39 . A calcineurin-deficient strain of C. neoformans showed decreased pathogenicity against mice and silkworms 25 , 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. neoformans , the calcineurin pathway is involved in capsule production and melanin synthesis, which are responsible for evading host immunity 39 . A calcineurin-deficient strain of C. neoformans showed decreased pathogenicity against mice and silkworms 25 , 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed that the calcineurin pathway is involved in the pathogenicity of T. asahii against silkworms. The calcineurin in C. neoformans regulates gene expression via the dephosphorylation of the transcription factors 39 . Therefore, we assumed that the calcineurin in T. asahii also regulates the virulence-related gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the different responses observed was due to the different cell types used (A549 vs. BEAS-2B), but another possibility is that upper bronchial epithelial cells respond more effectively to acapsular (or a thinner capsule) cryptococcal cells compared to epithelial cells found in the lower alveolar epithelium. It has been shown that cryptococcal particles have a very small or no capsule upon inhalation, and rapidly induce capsular growth as they proceed down the airway ( 42 , 129 131 ). One final possibility stems from the limitations and drawbacks some researchers find in using the A549 cell line.…”
Section: Modeling Cryptococcal Infections and What Has Been Learnedmentioning
confidence: 99%
“…In C. neoformans, the calcineurin pathway is involved in capsule production and melanin synthesis, which are responsible for evading host immunity 42 . A calcineurin-de cient strain of C. neoformans showed decreased pathogenicity against mice and silkworms 25,43,44 .…”
Section: Discussionmentioning
confidence: 99%